Exploring exercise adherence and quality of life among veteran, novice, and dropout trainees - Gabay, Maor; Levi, Ofer; Petracovschi, Simona; Negrea, Cristian; Matichescu, Marius; Oravitan, Mihaela (Frontiers in Sports and Active Living, 2023)
The purpose of this study was to identify and reveal the different contexts, variables, and factors that may influence adherence to physical activity among veteran, novice, and dropout trainees, such as the frequency of the weekly training units, the trainees preferred type of exercise, the purpose of the physical activity, and the relationship between support and supervision by fitness instructors and professionals. This study also examined the relationships between trainees seniority and the strength of the habit and adherence to physical activity, the effects of personal variables such as age and gender on adherence to physical activity, and how the seniority and adherence of trainees may affect their quality of life.